3x+4*7-3z=-46

Simple and best practice solution for 3x+4*7-3z=-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4*7-3z=-46 equation:


Simplifying
3x + 4 * 7 + -3z = -46

Multiply 4 * 7
3x + 28 + -3z = -46

Reorder the terms:
28 + 3x + -3z = -46

Solving
28 + 3x + -3z = -46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + 3x + -28 + -3z = -46 + -28

Reorder the terms:
28 + -28 + 3x + -3z = -46 + -28

Combine like terms: 28 + -28 = 0
0 + 3x + -3z = -46 + -28
3x + -3z = -46 + -28

Combine like terms: -46 + -28 = -74
3x + -3z = -74

Add '3z' to each side of the equation.
3x + -3z + 3z = -74 + 3z

Combine like terms: -3z + 3z = 0
3x + 0 = -74 + 3z
3x = -74 + 3z

Divide each side by '3'.
x = -24.66666667 + z

Simplifying
x = -24.66666667 + z

See similar equations:

| -6+3(9-7)= | | b=1/2f*p | | 17+13f=14 | | -3y+7=-6y | | 17+13f=15 | | 7x=8x+3 | | 14+3z=-47 | | x^8=i | | x/7=(x/8)-7 | | log(i+1)=0 | | loge(i+1)=0 | | ln(i+1)=0 | | (2r/3s)(9s/4r^2 | | x+12z=-81 | | 6=3/2*6-1/2 | | x^2+y^2-32x-60y+1122=0 | | 0=l^2+4l-572 | | 7*15+13y+z=105 | | 7x+13y+z=105 | | 70+6y+195=-125 | | (16-12-6x-15)/(6x-6)=5/18 | | (-11-6x)/(6x-6)=5/18 | | a+31=6 | | -30+17+9= | | c=0.5x^2+8x+11 | | (5x+7)(2x-14)=6 | | -8x-6=42 | | -11x+4x= | | 0.01/1500 | | cos(a)=0 | | 2y+3=y+3 | | 8x^2+34x+36=0 |

Equations solver categories